Ultrafast Dynamics of Photogenerated Electrons in CdS Nanocluster Multilayers Assembled on Solid Substrates: Effects of Assembly and Electrode Potential. Issue 10 (10th July 2013) - Yagi, Ichizo; Mikami, Kensuke; Okamura, Masayuki; Uosaki, Kohei
Abstract The ultrafast dynamics of photogenerated electrons in multilayer assemblies of CdS nanoparticles prepared on quartz and indium–tin oxide (ITO) substrates were followed by femtosecond (fs) visible‐pump/mid‐IR probe spectroscopy. Based on the observation of the photoinduced transient absorption spectra in the broad mid‐IR range at the multilayer assembly of CdS nanoparticles, the occupation and fast relaxation of higher electronic states (1Pe) were clarified. As compared with the electron dynamics of isolated (dispersed in solution) nanoparticles, the decay of photoexcited electrons in the multilayer assembly was clearly accelerated probably due to both electron hopping and scattering during interparticle electron tunneling. By using an ITO electrode as a substrate, the effect of the electric field on the photoelectron dynamics in the multilayer assembly was also investigated in situ. Both the amplitude and lifetime of photoexcited electrons gradually reduced as the potential became more positive. This result was explained by considering the reduction of the interparticle tunneling probability and the increase in the electron‐transfer rate from the CdS nanoparticle assembly to the ITO electrode.